Wedding i-Planner - Zhang, Ruolangxing (Nanyang Technological University, 2020)
A Wedding is one of the most important days is one's life. Nowadays people want a unique wedding to themselves. Every couple's love story is different and they should feel free to celebrate their one and only day in the way they like. So Wedding i-Planner is for those who want to plan and design the event by themselves. The very first thought of the wedding i-planner was to really do the job of a physical "planner", but more flexibly and efficiently with timeline and budget tracking. That's where the middle pages ‘Coming Soon’ , ‘Going on’ , ‘Just Finished’ came from. Couples can freely add or delete tasks according to needs, make notes and track progress. Besides task management, budget planning is also one crucial aspect of a successful wedding. Individual page "i-Calculator" collects tasks spending automatically and reminds about remaining budget. Other side functions include Venue Tests and Guest Table Arrangement.